2012
DOI: 10.1002/jbt.21414
|View full text |Cite
|
Sign up to set email alerts
|

Antigenotoxic properties of two newly synthesized β‐aminoketones against N‐methyl‐N′‐nitro‐N‐nitrosoguanidine and 9‐aminoacridine‐induced mutagenesis

Abstract: The aim of this study was to determine the antigenotoxic potential of two newly synthesized β-aminoketones against N-methyl-N'-nitro-N-nitrosoguanidine (MNNG) and 9-aminoacridine (9-AA)-induced mutagenesis. The mutant bacterial tester strains were MNNG-sensitive Escherichia coli WP2 uvrA and 9-AA-sensitive Salmonella typhimurium TA1537. Both test compounds showed significant antimutagenic activity at various tested concentrations. The inhibition rates ranged from 29.5% (compound 1: 2 mM/plate) to 47.5% (compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Noteworthy, the ability of compounds to affect mutagens simultaneously in varied ways significantly enhances antimutagenic effectiveness. Hence, searching for such multifunctionally acting antimutagens is of great importance [9].…”
Section: Multifunctionally Acting Antimutagensmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthy, the ability of compounds to affect mutagens simultaneously in varied ways significantly enhances antimutagenic effectiveness. Hence, searching for such multifunctionally acting antimutagens is of great importance [9].…”
Section: Multifunctionally Acting Antimutagensmentioning
confidence: 99%
“…The results showed that tannic acid can act as an anticlastogen and antimutagen in vivo [42]. (Figure 15) [9]. The antimutagenic potential of these compounds may be related to the inhibition of the production of O6-methylguanine, a product of MNNG that is related to its mutagenic effect.…”
Section: Tannic Acidmentioning
confidence: 99%
“…In the study conducted by Ozturkcan et al (2012), the antigenotoxic potential of two newly synthesized β-aminoketones against MNNG and 9-aminoacridine (9-AA)-induced mutagenesis was evaluated. The findings of the study provided information about chemical prevention from the toxicity of both mutagens by using selected compounds.…”
Section: Antimutagens With Multiple Mechanisms Of Actionmentioning
confidence: 99%
“…Certain antimutagens work by blocking the mutagen binding to DNA [33]. Two synthesized β-amino ketones have demonstrated their antimutagenic action against MNNG and 9-aminoacridine (9-AA) induced mutagenicity through this mechanism [33].…”
Section: Blockage Of Mutagen Binding To the Targetmentioning
confidence: 99%